Biodegradable polymer composite for cosmetic patch - Adli, Sarah Amalina; Ali, Fathilah; Azmi, Azlin Suhaida; Anuar, Hazleen; Hasham, Rosnani (Kulliyah of Engineering, International Islamic University Malaysia (IIUM)., 2019)
Patches has recently emerged and attracting more attention for its versatility in many areas such as cosmetic, pharmaceutical and medical. Patches can either be used to administer selected drug to skin or deliver some beneficial ingredients for cosmetic purposes. With that, as polymer is used as the matrix for patches, the polymer selected must be non-toxic, have adhesive property and non-irritative to the skin. Currently, synthetic polymer had been used as the matrix. However, as time passes, people are more concern with the environment, therefore biopolymer is chosen over synthetic polymer as they are degradable and also safe to use. Nowadays, as consumers are demanding for a more effective product that is not only good for appearance but also the health of the skin, studies had been done on many kinds of active ingredient that will give the best effect to the skin. Thus in this paper, patches made up of different combinations of polymer and active ingredients, as well as fabrication method currently used to produce patches will be discussed.